PENILAIAN STATUS VITAMIN A SECARA BIOKIMIA - Permaesih, Dewi (PERSATUAN AHLI GIZI INDONESIA, 2008)
VITAMIN A ASSESSMENT BY BIOCHEMICAL METHODSVitamin A has an important preventive effects on maternal and child mortality. Vitamin A deficiency(VAD) is one of the most devastating dietary deficiencies. Several methods are available to assessVAD. Tradisionally, clinical signs and symptoms of xerophthalmia were used to identify theseverity of population with vitamin A deficiency. Biochemical assessment methods availablewhich include serum retinol, serum retinol binding protein, serum retinyl ester, serum carotenoids,dose response test, the deuterated retinol isotope dilution test and breast milk retinolconcentrations. The determination of of retinol in blood (serum retinol concentrations) is one of themost frequently used methods, have been used extensively to identify populations at risk ofvitamin A deficiency. However, this method has several limitations. The major drawback of serumretinol is taking blood samples are required. Beside that, serum retinol is decreased only in severVAD, when liver stores are nearly exhausted. Because the majority of vitamin A in the body isstored in the liver, then the tests to measure vitamin A stores should be developed in order toknow the vitamin A status. Vitamin A concentration in breast milk is a prospective indicator ofVAD. Breast milk collection is less invasive and usually easier than blood drawing, do not have tobe further processed at the field station, thus shortening sample preparation. For the futureindicator of vitamin A, methods that are in development include using isotope dilution.Keywords: breast milk retinol, serum retinol, vitamin A analysis